UNDERESTIMATED IMPORTANCE AND STATUS OF THE SPECIALIST AT THE STAGE OF PRE-TRIAL INVESTIGATION - Лихова, Софія Яківна; Расторгуєв, Олександр Валерійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to define and outline the problem of uncertainty of a specialist as a participant in a pre-trial investigation. Methods: the methodological basis of the research was general scientific methods of cognition, with which the author tried to find out the procedural status of the specialist, his rights and responsibilities at the stage of pre-trial investigation. Results: the author identifies and sees the need for greater specification of the status of the specialist, his rights and responsibilities at the stage of pre-trial investigation. Discussion: the author proposes to comprehend the underestimated importance and status of a specialist at the stage of pre-trial investigation. The current Criminal Procedure Code of Ukraine is among certain participants in criminal proceedings who have or are obliged to have and possess scientific, technical and special knowledge and skills in the use of technical or other means of a specialist and expert. Unfortunately, the CPC of Ukraine does not have special norms, which enshrined general and consolidated provisions that would regulate the activities of both the specialist and the expert as participants in the pre-trial investigation. We have only fragmentary references to their procedural rights and responsibilities. The only clearly defined emphasis is the emphasis on the various goals of the involved specialist and expert, as well as on the procedural significance of the results obtained during the implementation of these special knowledge by these specialists. The thesis on the definition of the obligatory participation of a specialist in the conduct of investigative actions, during which special knowledge and skills of using technical or other means are used, is discussed.